Antibiotic Consumption and Deviation of Prescribed Daily Dose From the Defined Daily Dose in Critical Care Patients: A Point-Prevalence Study - Nunes, Patricia Helena Castro; Moreira, Jessica Pronestino de Lima; Thompson, Alessandra de Figueiredo; Machado, Thalita Lyrio da Silveira; Cerbino-Neto, José; Bozza, Fernando Augusto (Frontiers in Pharmacology, 2022)
Background: The consumption of antibiotics is one of the metrics used to evaluate the impact of antimicrobial stewardship programs (ASP). The aim of this study was to determine the prevalence of antibiotic consumption in Brazilian intensive care units (ICUs) and estimate the deviation of the prescribed daily dose (PDD) from the defined daily dose (DDD). Methods: This is a multicenter, observational, point-prevalence study carried out in adult ICUs of 8 Brazilian hospitals from August, 2019, to February, 2020. We collected data on the patient's demographic and clinical characteristics, antibiotic therapy, classification and site of infections. The DU90 (antibiotic accounting for 90% of the volume utilized) was calculated, and the antibiotics were classified by the Anatomical Therapeutic Chemical (ATC) Index and the World Health Organization (WHO) Access, Watch, Reserve (AWaRe) groups. For the most prevalent antibiotics, the deviation of PDD from DDD was determined. Results: Three hundred thirty-two patients from 35 ICUs were analyzed. The prevalence of antibiotic use was 52.4%. The patients in use of antibiotics were predominantly over 60 years of age (81.6%) with pulmonary infections (45.8%). A predominance of empirical regimens was observed (62.6%) among antibiotic therapies. The highest frequencies of prescriptions observed were for piperacillin+tazobactam (16.1%), meropenem (13.3%), amoxicillin+clavulanate (7.2%), azithromycin (7.2%), and teicoplanin (6.1%). The watch (64.2%) and reserve (9.6%) categories of the AWaRe classification accounted for 73.8% of all antibiotics, and they were prescribed alone or in combinations. High variability of doses was observed for the most prescribed antibiotics, and large deviations of PDD from the DDD were observed for meropenem, teicoplanin, and tigecycline. Conclusions: The high prevalence of antibiotic prescription was related to a predominance of empirical regimens and antibiotics belonging to the WHO Watch classification. The prescriptions also presented a high variability of doses and large deviations of PDD from DDD for meropenem, teicoplanin and tigecycline. The data suggest that the use of DDD may be insufficient to adequately monitor the consumption of meropenem, teicoplanin and tigecycline in the ICU population. The variability of doses found for the most prescribed antibiotics suggests the need for monitoring and intervention targets for antibiotic stewardship teams.